A systematic review of the utilization of artificial intelligence applications within the educational Oman systems - Al Husaini, Yousuf Nasser Said; Al Yahmadi, Hamed Hilal Nasser; Al Husaini, Mohammed Abdulla Salim (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the wake of rapid digital transformation and the increasing role of artificial intelligence (AI) in enhancing educational outcomes, this study investigates the integration of AI applications within the Omani educational portal under Oman’s Vision 2040. A systematic review was conducted using the Education Resources Information Center (ERIC) database, focusing on peer-reviewed articles published between 2020 and 2024. The six studies were selected for analysis following a rigorous screening process with defined inclusion and exclusion criteria. The findings indicate that AI is currently enhancing personalized learning, enabling data-driven decisionmaking, and supporting hybrid education platforms in Oman. These developments reflect the educational system’s readiness to adopt further AI technologies while directly contributing to the strategic priorities of Oman’s Vision 2040. This study provides important insights for decision-makers and educators looking to enhance the incorporation of advanced AI applications, thus revolutionizing educational practices and fostering sustainable national growth.